Hawkers’ Satisfaction with A Local Authority Water Meter Reading Management - Husin, Nor Azilah; Nazri, Nurul Nabilah (UUM Press, 2022)
This paper aims to identify hawkers' satisfaction with a local authority water meter reading management. Three years ago, the licensing and business development department installed meter readers at the hawker centres. Currently, water meter readers are no longer available, causing the department substantial losses. There are complaints on the use of bulk meters that the amount charged each month is indifferent. Several water meters in the hawker centres are not working correctly, resulting in difficulties by the authority to process the correct amount of water bills. The hawkers need to travel to the headquarters to make payment, making it more difficult. Hawkers are not happy because they have to pay the same amount though they might have consumed less than others. A total of 176 questionnaires was distributed to 500 hawkers in Kuala Lumpur City Hall (KLCH). Data were analysed using SPSS. The results showed that only one variable, water meter management, has a significant and weak relationship, influencing hawkers' satisfaction. This finding will give an excellent insight to the local authority in better control of water meter reading at hawker centres.